Nucleoside Analogues as Antibacterial Agents - Thomson, Jessica M.; Lamont, Iain L. (Frontiers in Microbiology, 2019)
The rapid increase in antibiotic-resistant bacteria has emphasised the urgent need to identify new treatments for bacterial infections. One attractive approach, avoiding the need for expensive and time-consuming clinical trials, is to re-purpose existing clinically-approved compounds for use as antibacterial agents. Nucleoside analogues are commonly used for treating viral and fungal infections, as well as for treating cancers, but have received relatively little attention as treatments for bacterial infections. However a significant number of clinically-approved derivatives of both pyrimidines and purines including halogenated, thiolated and azolated compounds have been shown to have antibacterial activity. In the small number of studies carried out to date such compounds have shown promise in treating bacterial infections. Here we review the mechanisms of action and antibacterial activities of nucleoside analogues that can potentially be repurposed for treating infections as well as considering possible limitations in their usage.